HUBUNGAN GAYA KEPEMIMPINAN KEPALA RUANGAN DENGAN KEPUASAN KERJA PERAWAT DI RUMAH SAKIT KHUSUS DAERAH PROVINSI MALUKU - Dewi Arwini Bugis; Nastain Pattimura; Rindiani Ali (Pasapua Health Journal, 2022)
Introduction: Leadership style can be interpreted as a way for a leader to influence other people or subordinates so that the person wants to do the leader’s will to achieve organizational goals even though personally this may not be liked (Tinambunan & Tampubolon, 2018). Job satisfaction is an emotional attitude that pleases and loves his job. This attitude is reflected by work morale, discipline, and work performance. Objective: To determine the relationship between the leadership style of the head of the room and the job satisfaction of nurses at the Ambon Regional Special Hospital (RSKD), Maluku Province. Method: Quantitative descriptive analytic with a cross sectional approach where data on independent variables and dependent variables will be collected at the same time (notoatmjo, 2012). Results :. From the results of the Chi Square test analysis of the Relationship between Head of Room Leadership Style and Nurse Job Satisfaction that 23 people (92.0%) were satisfied with 0 people (0.0%) dissatisfied. p = 0.440 > 0.05 means there is no significant relationship. Conclusion: Relationship between Head of Room Leadership Style and Job Satisfaction of Nurses that 23 people (92.0%) were satisfied with 0 people (0.0%) dissatisfied. It turns out that there is no significant relationship between Head of Room Leadership Style and Nurse Job Satisfaction.